HIstorical aspects of surgical treatment for colorectal cancer (literature review) - A. V. Dmitriev; V. S. Groshilin; A. V. Smolkina; L. S. Afunts; M. A. Kozyrevskiy; A. A. Uryupina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
The history of rectal cancer surgery dates back more than 200 years. This period encompasses many stages associated not only with the investigation of topographic and anatomical features and improvement of surgical techniques, but also with the implementation of modern medical equipment. Diagnostic tactics and surgical techniques for rectal cancer have been continuously studied and improved over the past several decades. This problem tends to be of particular interest due to an increased incidence of this disease and development of new technological approaches. Current studies are focused not only on patient's recovery, but also on the preservation of the good quality of life. An improvement in the quality of treatment is achieved by studying the surgical anatomy of the rectum, tumor morphological structure, risk factors, pathways of metastasis, and clinical course of the disease at different stages. Despite significant advances in rectal cancer surgery, there are still many unaddressed and controversial issues related not only to measures aimed to reduce the number of postoperative complications, but also wide implementation of sphincter-sparing surgeries along with following all the principles of radical intervention.